Computational Methods in Multiphase Flow VI 2011
DOI: 10.2495/mpf110021
|View full text |Cite
|
Sign up to set email alerts
|

Analogues of Rayleigh-Taylor and Richtmyer-Meshkov instabilities in flows with nonuniform particle and droplet seeding

Abstract: The well-known Rayleigh-Taylor (RT) and Richtmyer-Meshkov (RM) instabilities characterize the behavior of flows where two gases (or fluids) of different densities mix due to gravity (RT) or due to impulsive acceleration (RM). Recently, analogous instabilities have been observed in two-phase flows where the seeding density of the second phase, e.g., particles or droplets in gas, and the resulting average density, is initially non-uniform. The forcing causes the second phase to move with respect to the embedding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…In this paper, we study the interaction between a moving, normal shock and a perturbed curtain of particles. We show that the curtain exhibits instabilities that are very similar to RMI and RTI, however, as earlier research [8,9] indicates, these instabilities are non-baroclinic, but rather driven by interphase velocities and changes in number density in the particle phase. Here and further on, 'interphase velocity' refers to a velocity difference between the gaseous and particle phases.…”
Section: Introductionsupporting
confidence: 71%
“…In this paper, we study the interaction between a moving, normal shock and a perturbed curtain of particles. We show that the curtain exhibits instabilities that are very similar to RMI and RTI, however, as earlier research [8,9] indicates, these instabilities are non-baroclinic, but rather driven by interphase velocities and changes in number density in the particle phase. Here and further on, 'interphase velocity' refers to a velocity difference between the gaseous and particle phases.…”
Section: Introductionsupporting
confidence: 71%
“…One earlier study was also conducted for the multiphase analogue of RTI [5] for A m ~ 0.03. For the flow under investigation (air with a small volume fraction of micron-sized glycol droplets), it was concluded that morphologically and in terms of instability growth, the results were indistinguishable from classical single-phase RTI, with droplet seeding effectively contributing only to local average density.…”
Section: Introductionmentioning
confidence: 99%
“…Similar problems of interest (shock propagation through a combination of gases and non-gaseous inclusions) include coal dust explosions [3], supersonic combustion with fuel droplets [4], an interstellar gas or plasma with dust particles [5], and inertial confinement fusion (ICF) [6]. Far from behaving as passive tracers following the flow, particles or droplets can actually cause instability in the fluid after shock passage: this recently identified phenomenon is called a particle-lag instability (PLI) [7,8]. It occurs due to variations in the average density resulting from nonuniform initial distribution of the non-gaseous phase.…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary purposes of our experiments is to establish quantitative benchmarks for validation of numerical techniques. The authors have reported direct comparison of the experiments with simulations preformed with a multiphase code SHAMRC [8,9,10]. Anderson et al [10] demonstrated that careful modeling of initial conditions is required to reproduce experimental results.…”
Section: Introductionmentioning
confidence: 99%